Elderly Worker: Factors Influencing Elderly Work Participation in The Special Region of Yogyakarta - Sari, Nindya Purnama (International Journal for Disaster and Development Interface, 2026)
The Special Region of Yogyakarta was the first province in Indonesia to experience population aging. This study analyzed the participation rate of older adults in the workforce and the factors that influenced their decision to work. It used data from the 2024 National Labor Force Survey (Sakernas). Descriptive analysis showed that 69.26% of older adults remained active in the labor market, with the majority working in agriculture (48.25%) and holding informal jobs (84.84%). Their average income was far below the Provincial Minimum Wage. A total of 23.43% of older workers worked more than 48 hours per week, which could pose health risks. Logistic regression revealed that older men were 2.297 times more likely to work than women. Those with less education were 2.984 times more likely to remain employed than those with more education. Older people in rural areas were 2.940 times more likely to work than those in urban areas. However, the likelihood of older adults working decreased by 0.879 times with each additional year of age. Overall, the findings showed that older adults in Yogyakarta were highly dependent on informal employment, which tended to be inadequate in terms of job protection, working hours, and income.